2020
DOI: 10.1590/s0102-865020200080000006
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional laparoscopic Roux-en-Y gastric bypass with totally hand-sewn anastomoses for morbid obesity. A single center experience

Abstract: To assess the impact of three-dimensional (3D) vision use on operative time (OT) in laparoscopic Roux-en-Y gastric bypass (LRYGB) with hand-sewn anastomoses. Methods: We analyzed a prospectively collected database of patients who underwent LRYGB. We included all patients operated on with either 2D or 3D vision. Demographics and clinical characteristics, operative time, hospital stay and 30-day postoperative complications were collected for all patients and analyzed. Results: During the study time, out of 143 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…In other studies [ 2 , 12 ], no statistically significant values were observed for global complications, except for that by Padin et al, who analyzed the occurrence of complications based on the surgeon's experience at the beginning of the study. In this study, complications were recorded in the group of patients who were operated on by novice surgeons.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In other studies [ 2 , 12 ], no statistically significant values were observed for global complications, except for that by Padin et al, who analyzed the occurrence of complications based on the surgeon's experience at the beginning of the study. In this study, complications were recorded in the group of patients who were operated on by novice surgeons.…”
Section: Resultsmentioning
confidence: 95%
“…Another study was excluded because it was not conducted in English. Finally, only six studies [ 2 , 10 14 ] were included in the present meta-analysis based on the aforementioned inclusion criteria. These were all single-center studies including four prospective [ 10 13 ] and two retrospective [ 2 , 14 ] studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations